Menthol Targeting AMPK Alleviates the Inflammatory Response of Bovine Mammary Epithelial Cells and Restores the Synthesis of Milk Fat and Milk Protein - Liu, Songqi; Guo, Wenjin; Jia, Yuxi; Ye, Bojian; Liu, Shu; Fu, Shoupeng; Liu, Juxiong; Hu, Guiqiu (Frontiers in Immunology, 2021)
Mastitis is one of the most serious diseases that causes losses in the dairy industry, seriously impairing milk production and milk quality, and even affecting human health. Menthol is a cyclic monoterpene compound obtained from the stem and leaves of peppermint, which has a variety of biological activities, including anti-inflammatory and antioxidant activity. The purpose of this study was to investigate the preventive effect of menthol on the lipopolysaccharide-induced in-flammatory response in primary bovine mammary gland epithelial cells (BMECs) and its an-ti-inflammatory mechanism. First, BMECs were isolated and amplified from the udders of Hol-stein cows by enzymatic hydrolysis. BMECs were treated with menthol (10, 50, 100, 200 μM) for 1h, followed by lipopolysaccharide (5μg/ml) for 12 h.. Lipopolysaccharide treatment upregulated the protein levels of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (INOS) and the mRNA abundance of tumor necrosis factor α (TNF-α), interleu-kin-6 (IL-6), and interleukin-1β (IL-1β), while menthol was able to inhibit this effect. The inhibi-tory effect of menthol on proinflammatory factors was significantly reduced when autophagy was blocked using 3-Methyladenine (5μg/ml), an inhibitor of autophagy. Furthermore, lipopolysac-charide treatment reduced the expression levels of milk lipids and milk proteins, which were in-hibited by menthol. In addition, menthol (200 μM) treatment was able to significantly upregulate the expression level of autophagy-related protein LC3B, downregulate the expression level of P62, promote the expression abundance of autophagy-related gene mRNA, and enhance signifi-cantly enhance autophagic flow. Interestingly, treatment of BMECs with menthol (200 μM) pro-moted the phosphorylation of AMP-activated protein kinase (AMPK) and unc-51 like kinase 1 (ULK1) and increased the nuclear localization of nuclear factor-E2 associated factor 2 (Nrf-2). When the AMPK pathway was blocked using compound C (10μg/ml), an inhibitor of AMPK, au-tophagy was significantly inhibited. Autophagy levels were significantly decreased after block-ing the Nrf-2 pathway using ML385 (5μg/ml), an inhibitor of Nrf-2. Overall, the data suggest that menthol activates the AMPK-ULK1 pathway to initiate the onset of autophagy and maintains the level of autophagy through the AMPK-Nrf-2 pathway. In conclusion, the findings suggest that menthol may alleviate the inflammatory response in BMECs via the AMPN/ULK1/Nrf-2/autophagy pathway.